Inhibitory Effects of Raw-Extract Centella asiatica (RECA) on Acetylcholinesterase, Inflammations, and Oxidative Stress Activities via In Vitro and In Vivo - Hafiz, Zetty Zulikha (Molecules, 2020)
Centella asiatica (C. asiatica) is one of the medicinal plants that has been reported to exert comprehensive neuroprotection in vitro and in vivo. In view of this, the present study was performed to investigate the effect of ethanolic extract of C. asiatica, designated as raw-extract of C. asiatica (RECA) in reducing the acetylcholinesterase (AChE), inflammations, and oxidative stress activities via both in vitro (SH-SY5Y and RAW 264.7 cells) and in vivo (Sprague Dawley rats). Quantitative high-performance liquid chromatography analysis reveals that RECA contains a significantly high proportion of glycosides than the aglycones with madecassoside as the highest component, followed by asiaticoside. Treatment of SH-SY5Y cells with RECA significantly reduced the AChE activity in a concentration-dependent manner with an IC(50) value of 31.09 ± 10.07 µg/mL. Furthermore, the anti-inflammatory and antioxidant effects of RECA were evaluated by lipopolysaccharides (LPS)-stimulated RAW 264.7 cells. Our results elucidated that treatment with RECA significantly suppressed the level of pro-inflammatory cytokine/mediators and oxidative stress released in a concentration-dependent manner. Interestingly, these patterns of inhibition were consistent as observed in the LPS-induced neuroinflammation Sprague Dawley rats’ model. The highest concentration used in the two models presented the most significant results. Herein, our findings strongly suggest that RECA may offer therapeutic potential for the treatment of Alzheimer’s disease through inhibiting the AChE, inflammation, and oxidative stress activities.